Interleukin-27 levels in patients with myasthenia gravis - Liu, Xiao-Jiao (Transl Neurosci, 2020)
Interleukin-27 (IL-27), which belongs to IL-12 family, influences the function of T cells (Tregs) through regulating the expression, and function of forkhead box P3 (FoxP3). In this study, we detected the IL-27 serum levels in 59 myasthenia gravis (MG) patients and 35 healthy controls (HCs). Among them, 32 MG patients received immunoglobulin intravenous (IVIG) injections (0.4 g/kg per day for 5 consecutive days). IL-27 levels were collected before and after the treatments and subjected to a comparative study. Finally, we assessed the correlations of IL-27 levels with the clinical characteristics of MG. As a result, serum IL-27 levels were significantly higher in MG patients than those in the HCs. Meanwhile, significant reduction was detected after the IVIG treatment. IL-27 levels positively correlated with both MG activities of daily living and quantitative MG score. IL-27 may participate in the pathogenesis of MG and can be used as an early marker for the diagnosis and prognosis of MG. In addition, IL-27 can be used as a target for MG treatment through the regulation of specific immune signaling and maintaining immune homeostasis.